Electrocardiographic parameters and features of ventricular arrhythmias in various arrhythmogenic cardiomyopathy forms in the pediatric population: a systematic review and meta-analysis - D. Yu. Alekseeva; O. А. Kofeynikova; D. I. Marapov; E. S. Vasichkina (Российский кардиологический журнал)
Arrhythmogenic cardiomyopathy (ACM) is a rare genetic disease characterized by the development of life-threatening ventricular arrhythmias and impaired ventricular systolic function due to fibrofatty infiltration of the myocardium. Currently, the Task Force 2010 criteria and the Padua criteria are proposed for the diagnosis of this disease. However, despite the multiparametric approach, there are certain limitations of the presented algorithms for disease establishment, especially in children. Carrying out such high-tech diagnostic methods as endomyocardial biopsy and magnetic resonance imaging is extremely difficult in the pediatric population. In this regard, the study and application of electrocardiography becomes extremely relevant in children. In addition, there are no data on the features of ventricular arrhythmias in ACM in the pediatric population. In this systematic review with meta-analysis, we studied the features of ventricular arrhythmias and electrocardiographic parameters in various ACM types.